2021
DOI: 10.1038/s41598-021-85376-2
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and constraints on offshore foraging in harbour seals

Abstract: Central place foragers are expected to offset travel costs between a central place and foraging areas by targeting productive feeding zones. Harbour seals (Phoca vitulina) make multi-day foraging trips away from coastal haul-out sites presumably to target rich food resources, but periodic track points from telemetry tags may be insufficient to infer reliably where, and how often, foraging takes place. To study foraging behaviour during offshore trips, and assess what factors limit trip duration, we equipped ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Otters fed exclusively on freshwater species while harbour seals preyed on both freshwater and marine fish species. The observed lower dietary richness in otters is a result of their smaller range, usually based around freshwater habitats (Krawczyk et al, 2016) while seals are known to forage inshore and offshore, as well as in freshwater bodies, especially harbour seals (Vance et al, 2021). Recent sightings of Eurasian otters on Sylt and Fehmarn indicate that otters fed there locally prior to death which means a marine diet in some individuals can be expected (A. Drews, personal communication, 4 October 2021; Rohner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Otters fed exclusively on freshwater species while harbour seals preyed on both freshwater and marine fish species. The observed lower dietary richness in otters is a result of their smaller range, usually based around freshwater habitats (Krawczyk et al, 2016) while seals are known to forage inshore and offshore, as well as in freshwater bodies, especially harbour seals (Vance et al, 2021). Recent sightings of Eurasian otters on Sylt and Fehmarn indicate that otters fed there locally prior to death which means a marine diet in some individuals can be expected (A. Drews, personal communication, 4 October 2021; Rohner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis to explain this finding could likely be a higher uptake rate of prey species in adults than in younger individuals, and the increased energy needs for gestation and lactation [ 55 ]. Moreover, feeding quantity, the feeding behaviour, or favoured prey and foraging area differs between sexes, ages and species, as well as individual seals in general [ 10 , 11 , 12 , 13 ]. Hence, the exposure of MP and thus the presence in the GIT prior excretion can vary.…”
Section: Discussionmentioning
confidence: 99%
“…First evidence of the MP burden in the main regularly occurring top predator species are given in studies focusing on marine mammals found along the German and Dutch coastline; two studies investigated harbour porpoises [14,15] and another pilot study examined a small sample size of harbour seals and grey seals [16]. The aforementioned studies are comparable with examinations on porpoise and seal carcasses or scat samples which were conducted around the coastline of Great Britain and Ireland [17][18][19], since marine mammals are highly mobile within the NS and adjacent waters [13,20]. Knowledge on the MP occurrence in marine mammals, especially on seal species inhabiting the BS, which is known to be impacted by contaminants [21], is still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We inferred prey encounter events from the accelerometer data while animals were at sea. In coastal waters, harbour seals most frequently dive to the seabed and perform U-shaped dives through all phases of their foraging trips [52,53]. Therefore, we used accelerometery data to detect prey encounters during the bottom phase of each of these dives [53], characterized as the period when seals were within 20% of the maximum dive depth [54].…”
Section: (D) Prey Encountersmentioning
confidence: 99%